Proposta de metodologia para a otimização do gerenciamento do combustível retirado de usinas nucleares utilizando dry-casks - Gomes, Ian Bortolotti (2018)
The management of spent nuclear fuel elements removed from nuclear reactors is a priority subject among member states of the International Atomic Energy Agency. For the majority of these countries, the destination of such fuel elements is a decision that is yet to be made and the “wait-and-see” policy is thus adopted by them. In this case, the irradiated fuel is stored in the initial spent fuel pools until the power plant is decommissioned or, when there is no more rack space, they are stored in intermediate storage facilities, which can be another pool or dry storage systems, until the final decision is made. The purpose of this thesis is to propose a methodology that, using an optimization algorithm, determines the ideal time for the removal of the fuel elements from the spent fuel pool and the transference of them to dry-casks for intermediate storage. The methodology allows for the optimal dimensioning of the designed spent fuel pools and the cask characteristics, reducing the costs of purchasing new nuclear power plants. After the description of the methodology, an example of its application is presented, from which it is possible to observe that, using real-life data, the proposed methodology can become a valuable tool for making nuclear energy a more competitive choice.